SOURCES OF LONG TERM FUNDING - Adinda Purnama Sari; Fitria Lestari Pujiastuti; Harry Setiawan; Indrayani; Damsar; Muammar Khaddafi (PT. Radja Intercontinental Publishing, 2023)
Long-term funding is loan funds that have a tenor of more than one year. So companies that take long-term funding have more than one year to pay it off. Generally long-term repayment of funding ranges from 5 to 20 years. For companies, this type of funding is considered suitable as capital to start a business, or as a solution when large costs are needed in a short time. Sources of long-term funds are very useful for ensuring the survival of the company, through the capital market. Formation of capital and accumulation of funds aimed at increasing public participation in mobilizing funds to support national development financing. The existence of this institution is not only as a vehicle for sources of financing, but as an investment involving all potential public funds, both available domestically and abroad. For example, a company that wants to develop a business such as wanting to buy fixed assets in the form of land